Referentes iconográficos de X, un manga posmoderno: entre el Apocalipsis y el yin-yang - Castelli Olvera, Sarahi Isuki (El Colegio de México, 2018)
In this article, we analyze the iconographic and narrative features of the Japanese manga X (Ekkusu) created by clamp, published in Mexico by Editorial Vid between 2003 and 2005. We propose that the X manga has elements of the postmodern aesthetic in its history and graphics, with a focus on some religious aspects, shown in the hybrid manga way. This work is based on the iconographic analysis of the work, informed by the ideas of Omar Calabrese in Neo-Baroque. A sign of the times, and Fredric Jameson’s Cultural turn: selected writings on the postmodernism.